A Comparative Study of Internal and External Assets and Teachers' Professional Performance: Insights from English Language Teachers in the context of Iran - Leila Anjomshoa; mehri Hadadnarafshan (Comparative Education Society of Iran ( CESIR), 2019)
Teaching foreign/second languages is a demanding occupation, with levels of challenge increasing for teachers across the universe. Given that language teachers' awareness of their profession and a pleasant sense of job performance are central to their ability to teach well, the current study explores internal and external assets, both of which have been demonstrated to play a prominent role in educational contexts by looking into the classroom performance. The research aimed to explore teachers' reflections on teaching profession and the challenges they experience during their professional performance in the English as a foreign language (EFL) context of Iran. In this regard, the study adopted qualitative data collection procedures, and the work took place over a period of three months. Data were obtained from interviewing 50 teacher participants, who were selected according to the convenience sampling. The study findings indicate that we need more research and reflections on assets that underlie English teachers' performance. In effect, a complete awareness of performance could provide teachers with a more effective form of professionalism.Results point to the need to a clear understanding of challenges experienced by English language teachers in Iran as they contribute to this stressful profession. Given the fundamental role(s) played by teachers, it is promising that the current research contributes to a better understanding of how language teachers can develop in their profession.